Enhances production of coffee (Coffea robusta): The role of pollinator, forages potency, and honey production from Tetragonula sp. (Meliponinae) in Central Lombok, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Supeno B, Erwan, Agussalim. 2021. Enhances production of coffee (Coffea robusta): The role of pollinator, forages potency, and honey production from Tetragonula sp. (Meliponinae) in Central Lombok, Indonesia. Biodiversitas 22: 4687-4693. The bees role as an agent of pollinators to improve the productivity of plants. This study was purposed to enhance coffee production (Coffea robusta) by roles of stingless bee Tetragonula sp. as pollinator agent, forages potency, and honey production. This study has been conducted in a coffee plantation in Lantan, Central Lombok, Indonesia. Several parameters were measured such as the number of bunches and flowers, production of nectar and pollen, sucrose nectar content, production of coffee, production of honey, honey stomach volume, and pollen weight. The results showed that the different observation time influenced the number of bunches, flowers, production of nectar and pollen, sucrose nectar content (P
Keywords: Biodiversity; coffee flowers; nectar; pollination; pollen